Mucormycosis: Pathogenesis, Diagnosis, and Management - Rauthan, Pratibha; Sharma, Deepak Chand (Asian Journal of Pharmaceutical Research and Development, 2021)
Mucormycosis (black fungus) is caused by Mucor and Rhizopus. After getting affected such warning signs; pain and redness around the eyes and nose, fever, headache, coughing, shortness of brain, bloody vomit can see. It can suspect in COVID-19 patients, diabetics, or immunosuppressed individuals. Mucormycosis, if not cared it may be turned fatal. Mucormycosis can cause different types of infections: rhino-cerebral, pulmonary, cutaneous, gastrointestinal, and dissemination mucormycosis. In a study β- hydroxybutyrate (a representative of ketone bodies) and elevated serum iron levels were the major factors that enhanced expression of both CotH and GRP78, whereas lactic acidosis did not affect their expression. In addition, sodium bicarbonate reversed the effect of acidosis and protected β- hydroxybutyrate –treated mice from mucormycosis, implying the significance of correction acidosis as a treatment measure in patients with DKA and mucormycosis. The objective of this paper is screening, different pathogenesis, diagnosis, and management of Mucormycosis. An additional factor that significantly contributes to the poor prognosis of these infections is the inherent resistance of Mucorales to the most available antifungals, with amphotericin-B, posaconazole, and isavuconazole considered the most potent antifungals in vitro. According to the studies Rhizopus arrhizus is present in 85% of rhino-cerebral forms, compared with only 17% of non-rhino cerebral forms. However, recent data enlarge the antifungal armamentarium with the US Food and Drug Administration and European Medicines Agency’s approval of the new triazole isavuconazole, however, comparative clinical data are lacking, and the respective places of polyenes and different azoles need to be discussed.